187 Mental health clusters during COVID-19 pandemic are associated with multiple dimensions of sleep in a sample of pregnant women. (3rd May 2021) - Lucchini, Maristella; Firestein, Morgan; Shuffrey, Lauren C; Pini, Nicolò; Babineau, Vanessa; Fifer, William P; Alcantara, Carmela
Abstract: Introduction: Sleep and mental health have a bidirectional relationship. During pregnancy, poor sleep health, depression and stress are common and have been associated with poor maternal and fetal outcomes. The COVID-19 pandemic has introduced additional physical and psychological risk factors, due to high mortality rate, and economic and social repercussions. This study examines whether prenatal maternal mental health clusters are associated with multiple dimensions of sleep during pregnancy in the context of the COVID-19 pandemic. Methods: From June-December 2020, participants were recruited as part of the COVID-19 Mother Baby Outcomes (COMBO) Cohort at Columbia University (N=188; at recruitment gestational age: 32.2±8.2 weeks; age: 32±6.75 years; N=74 Hispanic, N=65 White non-Hispanic, N=27 Black/African American, N=22 other). Survey data on maternal depression (PHQ-9), perceived stress (PSS), Covid-related stress, and sleep health (PSQI) were collected. Using hierarchical clustering, we created maternal mental health clusters (MMHC). Regressions analyses were implemented to estimate the associations between multiple dimensions of sleep based on MMHC. Results: derived three MMHC: Low-risk (no depression, no Covid-stress, low-moderate perceived stress), Covid-stress (no depression, moderate Covid-stress, low-moderate perceived stress) and high-risk (moderate depression, moderate Covid-stress, moderate to high perceived stress). Maternal age, gestational age, income, and race were not significantly different across clusters. The Covid-stress cluster compared to the low-risk cluster reported worse subjective sleep quality (ß=0.34±0.11, p=0.0025), longer sleep latency (ß=0.44±0.13, p<0.000), more sleep disturbances (ß=0.67±0.18, p=0.004) and an overall higher PSQI score (ß=0.32±0.13, p=0.017). Compared to the low-risk group, the high-risk group reported worse subjective sleep quality (ß=0.96±0.3, p<0.000), longer sleep latency (ß=0.79±0.13, p<0.000), shorter sleep duration (ß=0.67±0.18, p=0.0003), lower sleep efficiency (ß=0.67±0.25, p=0.008), more sleep disturbances (ß=0.59±0.10, p<0.000), higher daytime dysfunction (ß=0.85±0.10, p=0.000) and an overall higher PISQI score (ß=1.15±0.16, p<0.000). Conclusion: Our results indicate that the COVID-19 pandemic has affected mental health profiles during pregnancy, with evidence of a high-risk cluster presenting Covid-stress and depressive symptoms and a Covid-stress cluster presenting Covid-stress without depressive symptoms in a multi-ethnic sample of pregnant women. Both were associated with poorer sleep health outcomes compared to the low-risk cluster. These results have important implications for screening and treatment for the sleep health and obstetric communities during these unprecedented times. Support (if any):